DIAGNOSIS FOR THE IMPLEMENTATION OF AN ENVIRONMENTAL MANAGEMENT SYSTEM IN A MICROBUSINESS IN THE URBAN VECTOR AND PEST CONTROL SECTOR - Ribeiro, Renata Maciel; Barros, Sergio Ricardo; Wasserman, Julio Cesar; Franz, Barbara (Brazilian Journal of Operations & Production Management, 2016)
This project analyzes and discusses the application of a methodological valuation model of an environmental maturity of a company of vectors and pests control. The method used was the initial environmental diagnostics, which intended to classify in a scale of values the Business Process of the company to Certification based on NBR ISO 14001. As a result of the application of the method were identified EMS Critical Success Spots low performed by the company, and the positive influence of ISO 9001 Certification already established in the organization. As well as, proposed actions to improve the weaknesses that were identified by the diagnostics in order to establish a schedule for the compliance of the first phase of the PDCA method proposed by the ISO 14001.